Inflammatory signals directly instruct PU.1 in HSCs via TNF - Etzrodt, M; Ahmed, N; Hoppe, P; Loeffler, D; Skylaki, S; Hilsenbeck, O; Kokkaliaris, K; Kaltenbach, H; Stelling, J; Nerlov, C; Schroeder, T (American Society of Hematology, 2018)
The molecular mechanisms governing the transition from hematopoietic stem cells (HSCs) to lineage-committed progenitors remain poorly understood. Transcription factors (TFs) are powerful cell intrinsic regulators of differentiation and lineage commitment, while cytokine signaling has been shown to instruct the fate of progenitor cells. However, the direct regulation of differentiation-inducing hematopoietic TFs by cell extrinsic signals remains surprisingly difficult to establish. PU.1 is a master regulator of hematopoiesis and promotes myeloid differentiation. Here we report that TNF can directly and rapidly up-regulate PU.1 protein in HSCs in vitro and in vivo. We demonstrate that in vivo, niche-derived TNF is the principal PU.1 inducing signal in HSCs and is both sufficient and required to relay signals from inflammatory challenges to HSCs.